Gadoxetic Acid–Enhanced MR Imaging Predicts Simeprevir‐Induced Hyperbilirubinemia During Hepatitis C Virus Treatment: A Pilot Study. (22nd September 2016) - Okubo, Hironao; Kitamura, Tsuneo; Ando, Hitoshi; Fukada, Hiroo; Igusa, Yuki; Kokubu, Shigehiro; Miyazaki, Akihisa; Fujimura, Akio; Shiina, Shuichiro; Watanabe, Sumio
Abstract: Simeprevir is a substrate for organic anion‐transporting polypeptides (OATPs) that transport bilirubin. Hyperbilirubinemia is an adverse event reported during treatment of chronic hepatitis C patients with simeprevir plus pegylated interferon and ribavirin. Because gadoxetic acid is also a substrate of OATPs, pretreatment gadoxetic acid–enhanced magnetic resonance imaging (MRI) may predict hyperbilirubinemia during treatment. This prospective study therefore evaluated 11 consecutive patients with chronic hepatitis C who underwent gadoxetic acid–enhanced MRI prior to treatment with simeprevir plus pegylated interferon and ribavirin for 12 weeks, followed by pegylated interferon and ribavirin for an additional 12 weeks. Their contrast enhancement index (CEI), an index of liver parenchymal enhancement during the hepatobiliary phase, was assessed before treatment. Plasma trough concentrations (Ctrough ) of simeprevir were determined 7 days after its administration, and serum bilirubin concentrations were measured throughout the course of treatment. Six patients (55%) developed hyperbilirubinemia (≥1.6 mg/dL) during treatment. Ctrough was significantly higher in patients with than without hyperbilirubinemia ( P = .009), with a strong inverse relationship between CEI and Ctrough ( r = ‐0.911, P < .001). CEI was significantly lower in patients with than without hyperbilirubinemia ( P = .009), but there were no significant differences between the 2 groups in pretreatment serum albumin concentrations and FIB‐4 index, an index of liver fibrosis. Hepatic enhancement with gadoxetic acid was related to Ctrough of simeprevir. Gadoxetic acid‐enhanced magnetic resonance imaging may predict the development of hyperbilirubinemia during treatment of hepatitis C patients with simeprevir plus pegylated interferon and ribavirin.